2021
DOI: 10.1016/j.xfre.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of preimplantation genetic testing for aneuploidy for fresh donor oocyte cycles

Abstract: Objective: To determine whether in vitro fertilization (IVF) with preimplantation genetic testing for aneuploidy (PGT-A) is cost effective to achieve a live birth compared with IVF alone in fresh donor oocyte cycles. Design: Theoretical cost-effectiveness study. Setting: Not applicable. Patient(s): None. Intervention(s): Comparison between the cost of IVF with PGT-A vs. IVF alone to achieve a live birth. The model analyzed a hypothetical single fresh oocyte donor IVF cycle with PGT-A vs. IVF alone and followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…However, as full oocyte cohorts were not donated to one patient, it is not plausible to conclude that oocyte donors were impaired in the PGT-A cost-effective group. Moreover, Antero et al [27] showed that PGT-A is not cost-effective in IVF cycles when fresh oocyte donors in the same age range as the current study were used. PGT-A cost varies in different countries, and technology tends to be more expensive in developing countries [28].…”
Section: Discussionmentioning
confidence: 63%
“…However, as full oocyte cohorts were not donated to one patient, it is not plausible to conclude that oocyte donors were impaired in the PGT-A cost-effective group. Moreover, Antero et al [27] showed that PGT-A is not cost-effective in IVF cycles when fresh oocyte donors in the same age range as the current study were used. PGT-A cost varies in different countries, and technology tends to be more expensive in developing countries [28].…”
Section: Discussionmentioning
confidence: 63%
“…Among them, three studies [ 13 , 18 , 23 ] did not explain the research perspective; only three studies [ 16 , 18 , 22 ] stated that the discount rate was not set; the model types were defined in all the 12 studies, but Mathieu (2020) and van Eekelen (2021) did not provide a specific model structure diagram. There were no subgroups, heterogeneity analysis, and distribution effect analysis in nine studies [ 13 16 , 18 20 , 22 , 24 ], and there were no uncertainty analysis in two studies [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 16 19 , 21 , 23 ] restricted the age of patients. Further, six studies [ 13 , 15 , 16 , 20 , 21 , 24 ] limited the duration of treatment (the first IVF cycle) and treatment options (fresh/frozen embryo transfer). The patients in one study [ 18 ] had additional complications (endometriosis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the current costs of embryo biopsy and PGT-A, the procedure seems approximately cost neutral at worst and cost effective at best for patients who have enough embryos for more than 1 live birth. Cost effectiveness studies based on data more than 5 or 10 years or data from multiple centers may not be applicable to current practice at centers proficient in embryo biopsy and PGT-A [ 18 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%